How patients with laryngeal cancer evaluate their quality of life - Škvrňáková, Jana; Teichmanová, Lenka; Bártová, Iva (University of South Bohemia, 2019)
The aim of the study was to find out the quality of life in patients with laryngeal cancer after the treatment and to compare it with the quality of life of the general population of the same average age. Data collection was conducted through a cross-sectional quantitative survey using the standardized World Health Organization Quality of Life Questionnaire (WHOQOL-BREF), including the population standards for the age groups. Data collection was undertaken in patients treated at the Otorhinolaryngological Department. Data from 42 patients, with an average age of 70 (16 patients with permanent tracheostomy) were evaluated. A t-test was used for the statistical evaluation of the quality of life in patients after the treatment of laryngeal cancer and the general population of the same average age. We found out that patients displayed a higher quality of life in most areas of the WHOQOL-BREF (physical health, psychological health, social relationships, environment, and overall quality of life and health). A difference was found in the area of physical health, which patients rated lower than the other surveyed areas. The use of the paired t-test for equal and unequal variances demonstrated a statistically significant difference in the subjective WHOQOL-BREF assessment of the quality of life between patients after the treatment of laryngeal cancer and the general population of the given average age. From a practical point of view (clinical intervention), it cannot be clearly stated that the results of the quality of life of patients after the treatment of laryngeal cancer are significantly different from the values of the given average age population.
Jak hodnotí kvalitu života pacienti s karcinomem hrtanu
Keywords: laryngeal cancer; population standard for quality of life; quality of life; WHOQOL-BREF; karcinom hrtanu; kvalita života; populační norma kvality života; WHOQOL-BREF